Toughening Wet‐Spun Silk Fibers by Silk Nanofiber Templating. Issue 7 (14th January 2022) - Yao, Ya; Allardyce, Benjamin J.; Rajkhowa, Rangam; Hegh, Dylan; Qin, Si; Usman, Ken Aldren S.; Mota‐Santiago, Pablo; Zhang, Jizhen; Lynch, Peter; Wang, Xungai; Kaplan, David L.; Razal, Joselito M.
Abstract: Regenerated silk fibers typically fall short of silkworm cocoon fibers in mechanical properties due to reduced fiber crystal structure and alignment. One approach to address this has been to employ inorganic materials as reinforcing agents. The present study avoids the need for synthetic additives, demonstrating the first use of exfoliated silk nanofibers to control silk solution crystallization, resulting in all‐silk pseudocomposite fibers with remarkable mechanical properties. Incorporating only 0.06 wt% silk nanofibers led to a ≈44% increase in tensile strength (over 600 MPa) and ≈33% increase in toughness (over 200 kJ kg −1 ) compared with fibers without silk nanofibers. These remarkable properties can be attributed to nanofiber crystal seeding in conjunction with fiber draw. The crystallinity nearly doubled from ≈17% for fiber spun from pure silk solution to ≈30% for the silk nanofiber reinforced sample. The latter fiber also shows a high degree of crystal orientation with a Herman's orientation factor of 0.93, a value which approaches that of natural degummed B. mori silk cocoon fiber (0.96). This study provides a strong foundation to guide the development of simple, eco‐friendly methods to spin regenerated silk with excellent properties and a hierarchical structure that mimics natural silk. Abstract : An all‐aqueous method is presented to wet spin silk fibers with remarkable mechanical properties. By adding tiny amounts of exfoliated silk nanofibres (SN) to seed silk solution crystallization, fibers can be spun with excellent strength (>600 MPa) and toughness (>200 kJ kg −1 ). When drawn, these silk–silk pseudocomposite fibers exhibit a crystallite size and orientation approaching that of natural silk.